Spectrophotometric Determination of Penicillamine with 2,6-Dichlorophenolindophenol in Drug Formulations - Koty, Afraim; Sharma, Mukul; Khare, Bindu; Srivastava, Ashutosh (Asian Journal of Chemistry, 2010)
A simple, rapid and sensitive spectrophotometric method is described for the determination of penicillamine by 2,6- dichlorophenolindophenol (2,6-DCPIP), as the chromogenic agent in bulk drug and formulations. It produces a bluish green coloured compound with maximum absorbance 610 nm. Beer's law was obeyed in the concentration range 0.005-0.100 ppm with molar absorptivity 1.97 × 103 L/mol/cm and RSD 0.3-0.82 %. Statistical comparison of the results with those from the reference method reveals excellent agreement and accuracy and precision was ± 0.481 to ± 0.33 %. This method is also applied on the whole blood and serum samples collected from the confirmed patients. The reaction of penicillamine with 2,6-DCPIP was confirmed by FTIR and 1H NMR. The main advantage of 2,6-DCPIP was its stability as a reagent solution, resulting in reliable and reproducible results.